Supplier management and Year 2000 compliance : an approach to the supplier management process and legal implications - Malta Information Technology & Training Services L (MITTS Blata I-BajdaMT, 1999)
Groups together guidelines and methodologies on a best practice approach to tackling supplier issues and their legal implications within the context of organisation-wide year 2000 compliance programmes.